In Vitro Assessment of Biofilm Production, Antibacterial Resistance of Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter spp. Obtained from Tonsillar Crypts of Healthy Adults - Renata Viksne; Karlis Racenis; Renars Broks; Arta Olga Balode; Ligija Kise; Juta Kroica (Microorganisms, 2023)
Background and Objective: Tonsillar crypts can be considered a reservoir for a variety of bacterial species. Some bacterial species can be considered part of the normal oropharyngeal microbiota. The roles of other pathogens, for example, the so-called non-oral and respiratory pathogens Staphylococcus aureus, Klebsiella, Pseudomonas, and Acinetobacter spp., which have strong virulence factors, biofilm production capacity, and the ability to initiate infectious diseases, are unclear. The purpose of this study was to detect the presence of S. aureus, K. pneumoniae, P. aeruginosa, and Acinetobacter spp. within the tonsillar crypts of healthy individuals, and to analyze the pathogens’ biofilm production and antibacterial resistances. Results: Only common oropharyngeal microbiota were cultivated from 37 participant samples (40.7%). The most commonly isolated pathogenic bacterium was S. aureus, which was isolated in 41 (45%) participant samples. K. pneumoniae was isolated in seven (7.7%) samples, Acinetobacter spp. were isolated in five (5.5%) samples, and P. aeruginosa was isolated in two (2.2%) samples. Biofilm producers predominated among the pathogenic bacteria; 51 strains were biofilm producers, and among them, 31 strains were moderate or strong biofilm producers. The tested S. aureus, K. pneumoniae, P. aeruginosa, and Acinetobacter spp. strains were sensitive to commonly used antibiotics (amoxicillin–clavulanic acid, clindamycin, or ciprofloxacin). One of the isolated S. aureus strains was MRSA. Conclusions: Biofilm is a commonly observed feature that seems to be a naturally existing form of pathogenic bacteria colonizing human tissue. S. aureus, K. pneumoniae, P. aeruginosa, and Acinetobacter spp. occasionally occur in the tonsillar crypts of healthy individuals, and, therefore, it is most likely that S. aureus, K. pneumoniae, P. aeruginosa, and Acinetobacter spp. in opportunistic tonsillar infections originate from the tonsillar crypt microbiota.